ZnO@Ag microspheres used as the anodic materials of superior alkaline rechargeable Zn–Ni batteries. Issue 10 (July 2020) - Rong, Yao; Yang, Zhanhong; Deng, Lie; Fu, Zhimin
Abstract: Alkaline zinc-nickel batteries have attracted the attention of many researchers because of their safety, environmental friendliness and low cost. However, the low utilization rate of active substances and poor conductivity lead to the decrease of battery capacity and poor cycling stability, which hinder its further development. Herein, an excellent cyclic stability zinc-nickel battery system with a ZnO@Ag microspheres anode has been developed. The ZnO@Ag microspheres deliver a high specific capacity over 620 mAh g −1 at 1C and of 94.08% coulombic efficiency before 700 cycles. The hydrothermal reaction time and the optimum amount of silver are also studied. This study demonstrates that the ZnO@Ag microsphere is emerging as a promising anodic material for the high-potential rechargeable aqueous zinc-nickel battery, and it may shed light on the high-performance anodic material for zinc-nickel battery storage devices.